perancangan Perancangan Sistem Informasi Masjid Berbasis Website (Studi Kasus MasjidJami Al-Mukaromah): pendahuluan - dendy pratama dendy pratama (CV. Multi Kreasi Media, 2022)
Al-Mukaromah Mosque is one of the large mosques in Pamulang, Al-Mukaromah Mosque does not yet have an information system in managing mosque activities and finances. The multitude of activities on Al-Mukaromah mosque and mosque financial management that has not been properly organized as well as manual data processing makes mosque administrators difficult processing data. To solve this problem, a management system is needed which can be accessed easily by mosque administrators and provide information precise, fast and accurate regarding the activities and finances of the Al-Mukaromah Mosque to the public On this basis, an information system was developed web-based mosque management using Hypertext Preprocessor (PHP), codeigniter framework and MySQl database which aim to make things easier mosque administrators in managing financial data and mosque activities and will make it easier for people to find mosque information through the website system which exists. The stages of this research include needs analysis, system design, implementation and testing. Al-Mukaromah Mosque management information system tested with black box testing methods and user testing. Based on testing that is done states all functions in the system are running well and 90% of respondents stated that the appearance of the website was attractive and easy to understand.